2016
DOI: 10.1519/ssc.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Complex Training for Power Development: Practical Applications for Program Design

Abstract: THE SHORT-TERM GAINS IN POWER AND RATE OF FORCE DEVELOPMENT AFTER MAXIMAL OR HIGH-INTENSITY DYNAMIC EXERCISES ARE THOUGHT TO RESULT FROM POSTACTIVATION POTENTIATION (PAP). THE MAJOR FACTORS AFFECTING PAP UTILIZATION ARE THE OPTIMAL INTRACOMPLEX RECOVERY, TRAINING STATUS, AND STRENGTH LEVELS OF THE ATHLETES. STUDIES HAVE SHOWN THAT WITH THE IDEAL COMBINATION OF MODERATELY HIGHLY TRAINED ATHLETES AND ADEQUATE INTRACOMPLEX RECOVERY, IT IS POSSIBLE TO EFFECTIVELY IMPLEMENT COMPLEX TRAINING FOR POWER DEVELOPMENT. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…All SCCs reported programming plyometric exercises which were predominantly prescribed all year round (66%), similar to previous surveys in NHL (12), NBA (37), wrestling (14) and rugby union (21). Whereas, plyometrics were mostly prescribed before weights (40%) and as complex training (35%), which is in line with research on power development (24). It has been recommended using complex training for power development, where the short-term intrasession gains in power derive from post activation potentiation, whereas programming complex training within a training cycle has also shown increases in lower body power metrics such as peak ground reaction force during a countermovement jump (24,26).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…All SCCs reported programming plyometric exercises which were predominantly prescribed all year round (66%), similar to previous surveys in NHL (12), NBA (37), wrestling (14) and rugby union (21). Whereas, plyometrics were mostly prescribed before weights (40%) and as complex training (35%), which is in line with research on power development (24). It has been recommended using complex training for power development, where the short-term intrasession gains in power derive from post activation potentiation, whereas programming complex training within a training cycle has also shown increases in lower body power metrics such as peak ground reaction force during a countermovement jump (24,26).…”
Section: Discussionsupporting
confidence: 84%
“…It has been recommended using complex training for power development, where the short-term intrasession gains in power derive from post activation potentiation, whereas programming complex training within a training cycle has also shown increases in lower body power metrics such as peak ground reaction force during a countermovement jump (24,26). It should be noted that increases in lower body power have not shown differ significantly from when plyometrics and resistance training were performed separately, but complex training may be a more time efficient option for SCCs to implement in their program (22,24,26). The most commonly prescribed plyometric exercise in this study was multiple hops/lunges (84%).…”
Section: Discussionmentioning
confidence: 99%
“…However, research in professional soccer has suggested combining strength and plyometric training compared to strength training alone, shows no additional improvements to performance in strength, power and speed tests [ 36 ]. Nonetheless, complex training is a time efficient method for integrating strength and plyometric work within the same program [ 37 ]. Comparable to American football [ 15 ] multiple hops/lunges and bounding, were the most prescribed plyometric exercises in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the training density (number of repetitions per training unit) is low. The solution may be the approach proposed by Lim and Barley [ 47 ] consisting of the introduction of activity within the intra-(between CA and post-CA) and inter-complex (between sets of complex exercises) rest interval. These exercises should be of low intensity and should not be demanding due to the importance of the relationship between fatigue and potentiation in achieving the effect of performance enhancement.…”
Section: Post-activation Performance Enhancement and Complex Trainingmentioning
confidence: 99%
“…These exercises should be of low intensity and should not be demanding due to the importance of the relationship between fatigue and potentiation in achieving the effect of performance enhancement. It seems that the mobility (e.g., serratus anterior wall slides) or stability drills (e.g., seated marching on stability ball) proposed by the Lim and Barley [ 47 ] for muscle groups not involved in the complex would be appropriate. Consequent to these exercises, the elderly will be able to improve muscle balance, posture, and overall body coordination, which will open up a number of new exercises they will be able to perform in later phases of training, without extending workout time.…”
Section: Post-activation Performance Enhancement and Complex Trainingmentioning
confidence: 99%